Overlapping Roles of Yeast Transporters Aqr1, Qdr2, and Qdr3 in Amino Acid Excretion and Cross-Feeding of Lactic Acid Bacteria - Kapetanakis, George C.; Gournas, Christos; Prévost, Martine; Georis, Isabelle; André, Bruno (Frontiers in Microbiology, 2021)
Microbial species occupying the same ecological niche or codeveloping during a fermentation process can exchange metabolites and mutualistically influence each other’s metabolic states. For instance, yeast can excrete amino acids, thereby cross-feeding lactic acid bacteria unable to grow without an external amino acid supply. The yeast membrane transporters involved in amino acid excretion remain poorly known. Using a yeast mutant overproducing and excreting threonine (Thr) and its precursor homoserine (Hom), we show that excretion of both amino acids involves the Aqr1, Qdr2, and Qdr3 proteins of the Drug H+-Antiporter Family (DHA1) family. We further investigated Aqr1 as a representative of these closely related amino acid exporters. In particular, structural modeling and molecular docking coupled to mutagenesis experiments and excretion assays enabled us to identify residues in the Aqr1 substrate-binding pocket that are crucial for Thr and/or Hom export. We then co-cultivated yeast and Lactobacillus fermentum in an amino-acid-free medium and found a yeast mutant lacking Aqr1, Qdr2, and Qdr3 to display a reduced ability to sustain the growth of this lactic acid bacterium, a phenotype not observed with strains lacking only one of these transporters. This study highlights the importance of yeast DHA1 transporters in amino acid excretion and mutualistic interaction with lactic acid bacteria.